Industry of anonymity : inside the business of cybercrime - Lusthaus, Jonathan, 1984- (Harvard University Press, 2018)
Jonathan Lusthaus lifts the veil on cybercriminals in the most extensive account yet of the lives they lead and the vast international industry they have created. Having traveled to hotspots around the world to meet with hundreds of law enforcement agents, security gurus, hackers, and criminals, he charts how this industry based on anonymity works.--